Effect of Bariatric Weight Loss on the Adipose Lipolytic Transcriptome in Obese Humans - Shakun Karki; Melissa G. Farb; Samantha Myers; Caroline Apovian; Donald T. Hess; Noyan Gokce (Mediators of Inflammation)
Background. Dysregulated lipolysis has been implicated in mechanisms of cardiometabolic disease and inflammation in obesity. Purpose. We sought to examine the effect of bariatric weight loss on adipose tissue lipolytic gene expression and their relationship to systemic metabolic parameters in obese subjects. Methods/Results. We biopsied subcutaneous adipose tissue in 19 obese individuals (BMI 42 ± 5 kg/m2, 79% female) at baseline and after a mean period of 8 ± 5 months (range 3–15 months) following bariatric surgery. We performed adipose tissue mRNA expression of proteins involved in triglyceride hydrolysis and correlated their weight loss induced alterations with systemic parameters associated with cardiovascular disease risk. mRNA transcripts of adipose triglyceride lipase (ATGL), hormone-sensitive lipase (HSL), and lipid droplet proteins comparative gene identification 58 (CGI-58) and perilipin increased significantly after weight loss (p<0.05 for all). ATGL expression correlated inversely with plasma triglyceride (TG), hemoglobin A1C (HbA1C), and glucose, and HSL expression correlated negatively with glucose, while CGI-58 was inversely associated with HbA1C. Conclusion. We observed increased expression of adipose tissue lipolytic genes following bariatric weight loss which correlated inversely with systemic markers of lipid and glucose metabolism. Functional alterations in lipolysis in human adipose tissue may play a role in shaping cardiometabolic phenotypes in human obesity.